An Analysis of Branding at Islamic Universities Using Mark and Pearson’s Archetypes - Nur Asiyah; Robith Khoiril Umam; Yustin Sartika (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Competition between universities to gain market attention requires various strategies, including the activities of the institution's branding. University branding is obligatory to publicize their existence and values, which differ from competitors, whether in scientific values or other elements. However, sometimes stakeholders to not understand the "branding map" of the competitors surrounding campuses. This study aims to reveal the university's branding using the concept of archetypes written by Mark and Pearson. Twelve archetypes are commonly used for branding: the innocent, the explorer, the sage, the hero, the outlaw, the magician, the regular guy, the lover, the jester, the caregiver, the creator, and the ruler. The data in this research is in the form of text and pictures taken from logos, slogans, visions, and missions of 13 Islamic universities under the Ministry of Research, Technology and Higher Education and the Ministry of Religious Affairs. The study shows that nine of the twelve archetypes appear in Islamic universities. The nine archetypes are the sage, the caregiver, the creator, the explorer, the hero, the innocent, the ruler, the regular guy, and the lover. Each Islamic University has multiple archetypes at once. Therefore, campus branding used in marketing and publication programs can use the most dominating archetypes.